2010
DOI: 10.19182/bft2010.306.a20428
|View full text |Cite
|
Sign up to set email alerts
|

Dimension socioculturelle du baobab <em>Adansonia digitata</em> L. dans le plateau central du Burkina faso

Abstract: The baobab, Adansonia digitata L., is classified as one of the five priority woody species in Burkina Faso, where it is unevenly distributed across the agrarian landscape. However, the main socio-cultural determinants of the baobab's distribution are little known. This study therefore aimed to characterize the socio-cultural structure and factors determining the distribution of the baobab in the North Central and West Central regions of Burkina Faso. The studies were based on forest inventories, socio-economic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 4 publications
0
3
0
2
Order By: Relevance
“…Thus, trees are victims of extreme barking, pruning and cutting that compromise their long-term survival. For example, pruning can stop seed production of A. digitata [22]. Bélem et al [7] also noted that the exploitation of fruits, seeds or flowers could deprive species of seeds for regeneration.…”
Section: Use and Vulnerability Of Ligneous Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, trees are victims of extreme barking, pruning and cutting that compromise their long-term survival. For example, pruning can stop seed production of A. digitata [22]. Bélem et al [7] also noted that the exploitation of fruits, seeds or flowers could deprive species of seeds for regeneration.…”
Section: Use and Vulnerability Of Ligneous Speciesmentioning
confidence: 99%
“…Fruit tree species from which many ripen during that period and also species with edible leaves and flowers play a particularly important role for population food security [25,26]. S. senegalensis, B. aegyptiaca, L. hastata, V. paradoxa, L. microcarpa, A. digitata, B. senegalensis and A. macrostachya are part of these species that are deliberately kept in the village land areas for their nutritive role [8,22,25,27,28]. Our study revealed that five of the above species, together with six others, were the most used (VUET ≥ 6).…”
Section: Changes In the Use Of Ligneous Speciesmentioning
confidence: 99%
“…Ces arbres procurent aux communautés rurales des services écosystémiques, telle la production de biens alimentaires et médicinaux, de fourrage et de bois (Yaméogo et al, 2005 ;Belem et al, 2008 ;Ngom et al, 2014). Ils assurent également une contribution à la spiritualité (Bationo et al, 2010), et servent à fertiliser les sols (Zomboudre et al, 2005) et à atténuer les effets du changement climatique (Bayala et al, 2014).…”
Section: Introductionunclassified
“…En effet, dans ces zones, la forte densité et la vigueur des individus de ces deux espèces leur confèrent une dominance dans une végétation dominée par des microphanérophytes. Des résultats similaires ont été observés dans la Commune de Libori au Niger par Idrissa et al (2018) (Thiombiano et al, 2006;Glélé et al, 2008;Assogbadjo et al, 2009;Adjonou et al, 2010;Bationo et al, 2010). En effet, les plantules assurent l'avenir du peuplement et les sujets adultes assurent la production des semences pour le renouvellement du peuplement (Dan Guimbo et al, 2010;Adjonou et al, 2010).…”
Section: Discussionunclassified